Wortklassen - Engel, Ulrich (Studia Germanica Posnaniensia, 2018)
The aim of this article is to separate traditional morphological categories on the basis of uniform criteria in order to avoid problems of delimitation, classification and gaps. In the analysis of morphological categories (parts of speech, lexical units and other) two fundamental principles were adopted: l. Classification is based on word distribution in the widest sense of the word 2. Particular morphological categories are defined in a definite order, and each definition's character is that of a filter which distinguishes the relevant (appropriate) elements, whereas the other ones are transferred to the next filter. In this way fifteen morphological categories have been defined.